The mandate of the ECB: Legal considerations in the ECB's monetary policy strategy review - Michael Ioannidis; Sarah Jane Hlásková Murphy; Chiara Zilioli (European Central Bank (ECB), 2021)
This paper offers an overview of the mandate of the European Central Bank (ECB), as defined by its objectives, the instruments available to achieve them and the constitutional framework that the ECB shall observe in pursuing them. The objectives include the primary objective of maintaining price stability and the secondary objective of supporting the general economic policies in the Union. The price stability objective enjoys primacy amongst the ECB objectives. The Treaties do not provide for a hierarchy of the "general economic policies" that the ECB shall support, although a number of criteria derived from primary law can help in guiding the ECB's priorities in this respect. The ECB is also tasked with contributing to the "smooth conduct of policies pursued by the competent authorities relating to the prudential supervision of credit institutions and the stability of the financial system". As for the instruments available, these include both measures that directly pursue the objectives and measures that are instrumental in achieving them. Finally, the other constitutional rules that set out the framework within which the ECB pursues its objectives include the principles of conferral, institutional balance, proportionality, equal treatment and non-discrimination, as well as the principle of an open market economy and the prohibition of monetary financing.
Keywords: K23; G21; G28; 330; ECB mandate; ECB objectives; price stability; principle of conferral; principle of proportionality